Bioengineered miR-27b-3p and miR-328-3p modulate drug metabolism and disposition via the regulation of target ADME gene expression - Xin Li; Ye Tian; Mei-Juan Tu; Pui Yan Ho; Neelu Batra; Ai-Ming Yu (Elsevier, 2019)
Drug-metabolizing enzymes, transporters, and nuclear receptors are essential for the absorption, distribution, metabolism, and excretion (ADME) of drugs and xenobiotics. MicroRNAs participate in the regulation of ADME gene expression via imperfect complementary WatsonCrick base pairings with target transcripts. We have previously reported that Cytochrome P450 3A4 (CYP3A4) and ATP-binding cassette sub-family G member 2 (ABCG2) are regulated by miR-27b-3p and miR-328-3p, respectively. Here we employed our newly established RNA bioengineering technology to produce bioengineered RNA agents (BERA), namely BERA/miR-27b-3p and BERA/miR-328-3p, via fermentation. When introduced into human cells, BERA/miR-27b-3p and BERA/miR-328-3p were selectively processed to target miRNAs and thus knock down CYP3A4 and ABCG2 mRNA and their protein levels, respectively, as compared to cells treated with vehicle or control RNA. Consequently, BERA/miR-27b-3p led to a lower midazolam 1'-hydroxylase activity, indicating the reduction of CYP3A4 activity. Likewise, BERA/miR-328-3p treatment elevated the intracellular accumulation of anticancer drug mitoxantrone, a classic substrate of ABCG2, hence sensitized the cells to chemotherapy. The results indicate that biologic miRNA agents made by RNA biotechnology may be applied to research on miRNA functions in the regulation of drug metabolism and disposition that could provide insights into the development of more effective therapies. KEY WORDS: Bioengineered RNA, miR-27b, miR-328, CYP3A4, ABCG2, Drug disposition